A REVIEW ON: SECURITY TO PROFILE INFORMATION & PHOTOS OVER ONLINE SOCIAL NETWORK - DIPALI KHANDAGALE; PROF. PRAJAKTA SATARKAR (International Journal of Innovations in Engineering Research and Technology, 2021)
Now each day variouspersons are victimizationvariousapplications a number of them are social networking application whereanyonewill share their personal info, photos, videos, documents among friends over online Social Network(OSN). In recent years we have witnessed a significant growth of social-computingcommunities online services during which users share info in numerous forms. As content contributions from participants are crucial to the viability of those communities, it’s necessary to grasp what drives users to participate and share info with others in such settings. Online social networks such face book, orkut, twitter, whatsapp has setting to share the non-public info,photos videos over the networks. whereas such networks do allow users to manage what they share with whom, access management policies arenotoriously difficult to congure properly, this raises the question of whether or not OSN users’ privacy settings match their sharing intentions. Picture sharing is a pretty feature that popularizes online Social Networks (OSNs). Sadly, it should reveal user’s privacy if they’re permissible to post, comment, and tag a photograph generously. To handle this downside, numerous systems are explained which will be accustomed acknowledge everybody within the picture. For users of social networking sites like Facebook, this method focuses on the privacy considerations and wishes of the users, at an equivalent time explores concepts for privacy protection mechanisms by considering user’s current considerations and behaviors